PENGARUH DRAMA KOREA TERHADAP FASHION MAHASISWA UNIVERSITAS AL ASYARIAH MANDAR - Nurrahmadani Nurrahmadani; Sri Yuyun; Munawi Gay (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2020)
This study aims to determine the effect of Korean drama on student fashion at Al Asyariah Mandar University. The research uses a quantitative approach, using purposive sampling technique. The data obtained through questionnaires (skalah liker and the method of analysis of data determination (R). The results showed that there was an influence of Korean drama on student fashion by 33% (coefficients of detemination) while the remaining 67% was influenced by other variables not in this study.